Legal Protection for Student Victims of Bullying at SMPN 2 Ngawi - Fakhrina Wardina Athiroh; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2026)
This study aims to determine the implementation of legal protection for students who are victims of bullying in SMPN 2 Ngawi and to identify the inhibiting factors in providing such protection. The research method used is a juridical-empirical approach with primary data collection through semi-structured interviews with the Principal, Guidance and Counseling Teachers (BK), homeroom teachers, and students, while secondary data includes an analysis of various laws and regulations related to child protection and human rights. The results of the study indicate that the implementation of legal protection in SMPN 2 Ngawi is carried out through preventive channels such as socialization of rules of conduct, the formation of an Anti-Bullying Task Force, and strengthening religious character, as well as repressive channels through objective investigations, restorative mediation, and assertive counseling for victims which are substantially in line with Law No. 35 of 2014. However, the effectiveness of this protection still faces obstacles in the form of normalization of bullying actions.bullyingwhich is considered a joke, the victim's reluctance to report due to intimidation, and differences in perception between the school and the student's parents.